2016
DOI: 10.3389/fmicb.2016.00329
|View full text |Cite
|
Sign up to set email alerts
|

Infection with and Carriage of Mycoplasma pneumoniae in Children

Abstract: “Atypical” pneumonia was described as a distinct and mild form of community-acquired pneumonia (CAP) already before Mycoplasma pneumoniae had been discovered and recognized as its cause. M. pneumoniae is detected in CAP patients most frequently among school-aged children from 5 to 15 years of age, with a decline after adolescence and tapering off in adulthood. Detection rates by polymerase chain reaction (PCR) or serology in children with CAP admitted to the hospital amount 4–39%. Although the infection is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
2
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 102 publications
1
88
2
15
Order By: Relevance
“…In this study, four of five cases with a severe pleural effusion were school-aged children, and the lobar pneumonia pattern group also showed a higher CRP in school-aged children. Meyer et al suggested that an age-dependent amplification of inflammatory response may be a major factor of the M. pneumoniae-associated disease [19]. Narita et al reported that the severity of MP in children was associated with an increased serum level of interleukin (IL)-8 and IL-18 [20].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, four of five cases with a severe pleural effusion were school-aged children, and the lobar pneumonia pattern group also showed a higher CRP in school-aged children. Meyer et al suggested that an age-dependent amplification of inflammatory response may be a major factor of the M. pneumoniae-associated disease [19]. Narita et al reported that the severity of MP in children was associated with an increased serum level of interleukin (IL)-8 and IL-18 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Se estima que alrededor del 3-10% de los niños con infección por M. pneumoniae desarrollarán neumonía, y de estos, menos del 5% necesitarán hospitalización. 39 De los pacientes hospitalizados, hasta un 10% ingresa a unidad de cuidados intensivos (UCI).…”
Section: Epidemiologíaunclassified
“…y Canadá se encuentran en 13% y 12%, respectivamente. 39,40 Esto constituye un problema en el tratamiento de infecciones en pacientes pediátricos debido a que las alternativas terapéuticas como tetraciclinas, no son recomendadas para niños. 75 El mecanismo molecular de la resistencia se basa en mutaciones puntuales en el dominio V de la subunidad 23S del rRNA (posiciones 2058, 2059, 2062, 2611), lo que reduce la afinidad del antibiótico al ribosoma 69 y ocasionalmente también involucra mutaciones en las proteínas ribosomales L4 y L22.…”
Section: Tratamientounclassified
“…Childhood M.pneumoniae infection is complicated by different host-dependent characteristics; variable persistence of antibodies, missing IgM response after re-infection and infrequent production of IgA antibodies 5 . M. pneumoniae infection is less prevalent in infants in whom symptoms are milder 6 , while it predominantly occurs in children (5-15 years) 7 .…”
Section: Age/race In Mpneumoniae-associated Mersmentioning
confidence: 99%